ASD-1000: High-resolution, high-temperature acetylene spectroscopic databank. (November 2017) - Lyulin, O.M.; Perevalov, V.I.
Highlights: ASD-1000 is a high-temperature infrared spectroscopic C2 H2 databank. ASD-1000 contains calculated line parameters for the 3–10, 000 cm −1 spectral range. ASD-1000 can be used for temperatures up to 1500 K. ASD-1000 is freely accessible atftp.iao.ru/pub/ASD/ . Abstract: We present a high-resolution, high-temperature version of the Acetylene Spectroscopic Databank called ASD-1000. The databank contains the line parameters (position, intensity, Einstein coefficient for spontaneous emission, term value of the lower states, self- and air-broadening coefficients, temperature dependence exponents of the self- and air-broadening coefficients) of the principal isotopologue of C2 H2 . The reference temperature for line intensity is 296 K and the intensity cutoff is 10 −27  cm −1 /(molecule cm −2 ) at 1000 K. The databank has 33, 890, 981 entries and covers the 3–10, 000 cm −1 spectral range. The databank is based on the global modeling of the line positions and intensities performed within the framework of the method of effective operators. The parameters of the effective Hamiltonian and the effective dipole moment operator have been fitted to the observed values of the line positions and intensities collected from the literature. The broadening coefficients as well as their temperature dependence exponents were calculated using the empirical equations. The databank is useful for studying high-temperature radiative properties of C2 H2 . ASD-1000 is freely accessible via the Internet site of V.E. Zuev Institute of Atmospheric Optics SB RASftp://ftp.iao.ru/pub/ASD1000/ .